A Virulent Trueperella pyogenes Isolate, Which Causes Severe Bronchoconstriction in Porcine Precision-Cut Lung Slices - Qin, Lei; Meng, Fandan; He, Haijuan; Yang, Yong-Bo; Wang, Gang; Tang, Yan-Dong; Sun, Mingxia; Zhang, Wenlong; Cai, Xuehui; Wang, Shujie (Frontiers in Veterinary Science, 2022)
Abstract Trueperella pyogenes causes disease in cattle, sheep, goats and swine, and is involved occasionally in human disease worldwide. Most reports implicating T. pyogenes have been associated with clinical cases, whereas no report has focused on pathogenicity of T. pyogenes in mouse models or precision-cut lung slice (PCLS) cultures from swine. Here, we isolated and identified a virulent, β-hemolytic, multidrug-resistant T. pyogenes strain named 20121, which harbors the virulence marker genes fimA, fimE, nanH, nanP and plo. It was found to be highly resistant to erythromycin, azithromycin and medemycin. Strain 20121 was pathogenic in mouse infection models, displaying pulmonary congestion and inflammatory cell infiltration, partial degeneration in epithelial cells of the tracheal and bronchiolar mucosa, a small amount of inflammatory cell infiltration in the submucosa, and bacteria (>104 CFU/g) in the lung. Importantly, we used T. pyogenes 20121 to infect porcine precision-cut lung slices (PCLS) cultures for the first time, where it caused severe bronchoconstriction. Furthermore, dexamethasone showed its ability to antagonize bronchoconstriction in the same cultures, highlighting the need for bronchodilators to assist antibiotic treatment in T. pyogenes clinical infection. This is the first report of T. pyogenes used to infect and cause bronchoconstriction in porcine PCLS. Our results suggest that porcine PCLS cultures as a valuable 3D organ model for the study of T. pyogenes infection and treatment in vitro.